(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The main aim of the study is to identify the factors influencing purchase decision of FMCG products and know the consumer behaviour towards FMCG products in Tirunelveli District. The present study has been conducted with a view to analyze consumer behaviour towards FMCG products in Tirunelveli district. The sample size of the customer is 100 selected by the random sampling method. A structured questionnaire covering various aspects of general and the opinions of the sample consumer are collected for the present study. To equip further in this area secondary data are collected from various books, journals and libraries of various universities contributed much for this study. Tables are prepared with the help of primary data collected during the study period. Statistical tools such as ANOVA and ‘t’ test have also been used for the analysis of data. It is concluded that the Fast Moving Consumer Goods are consumed continuously by all the types of customers irrespective of the discrimination of the income, residence, status etc. Hence the researcher has enacted to describe the utility of all the manufacturers of Fast Moving Consumer Goods to sustain the market.